[The office after the German raid] (1914)
Inscription: "The office (afterwards)"--In pencil on reverse.
Part of collection: German raid on Cocos (Keeling Islands) and sinking of SMS Emden by HMAS Sydney, November 1914.
Title devised by cataloguer from inscription on reverse.
Also available online
Keywords: World War, 1939-1945 -- Cocos (Keeling) Islands -- Naval operations, German -- Photographs; World War, 1939-1945 -- Cocos (Keeling) Islands -- Amphibious operations -- Photographs